Training Women for Management: New Problems, New Solutions - Larwood, Laurie; Wood, Marion M.; Inderlied, Sheila Davis (Academy of Management Review, 1978)
Needs of women students and some programmatic changes potentially meeting those needs are considered. Analyses include discussion of the usefulness of female role models, pre-employment socialization, and segregated classrooms. Examples of programmatic changes now practiced in universities and business are presented. Finally, risks of developing programs are discussed with recommendations for continuing research.